Pengaruh Promosi Terhadap Volume Penjualan Tepung Terigu Kemasan Premium PT. XYZ - Prayogi, Juniar; Suroso, Arif Imam; Najib, Mukhamad (School of Business, Bogor Agricultural University (SB-IPB), 2023)
To be able to compete continuously in the market, PT. XYZ carries out promotions to increase sales volume of premium packaged flour products (CP Premium), including above the line and below the line promotion. This study aims to determine the effect of promotion on sales volume, analyze the effectiveness of the promotion, and provide recommendations referring to the results of the study. The research method used is descriptive quantitative and multiple regression analysis with the help of SPSS software. The type of data is secondary data in the form of time series sales volume and monthly promotion costs for the period 2013-2015. The steps used in multiple regression analysis are 1) Coefficient of Determination; 2) F test and 3) t test, with a significance level of 10%. The results of this study are the promotion costs above the line and below the line, affect the sales volume of CP Premium, and have an effect of 20.9% on sales volume. The results of the t-test (partial) show that the effective promotion categories are Others ATL (ATL) & Marketing Tools (BTL). Companies should increase promotional activities in the Others ATL and Marketing Tools categories because they have a significant effect on sales volume, evaluate other promotional categories, including trying promotions through TV commercials outside of peak season, and adding variations to internet promotions. Keywords: sales volume, multiple regression analysis, promotion effect, above the line promotion, below the line promotion